(x-1)(2x+6)=104

Simple and best practice solution for (x-1)(2x+6)=104 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-1)(2x+6)=104 equation:


Simplifying
(x + -1)(2x + 6) = 104

Reorder the terms:
(-1 + x)(2x + 6) = 104

Reorder the terms:
(-1 + x)(6 + 2x) = 104

Multiply (-1 + x) * (6 + 2x)
(-1(6 + 2x) + x(6 + 2x)) = 104
((6 * -1 + 2x * -1) + x(6 + 2x)) = 104
((-6 + -2x) + x(6 + 2x)) = 104
(-6 + -2x + (6 * x + 2x * x)) = 104
(-6 + -2x + (6x + 2x2)) = 104

Combine like terms: -2x + 6x = 4x
(-6 + 4x + 2x2) = 104

Solving
-6 + 4x + 2x2 = 104

Solving for variable 'x'.

Reorder the terms:
-6 + -104 + 4x + 2x2 = 104 + -104

Combine like terms: -6 + -104 = -110
-110 + 4x + 2x2 = 104 + -104

Combine like terms: 104 + -104 = 0
-110 + 4x + 2x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-55 + 2x + x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-55 + 2x + x2)' equal to zero and attempt to solve: Simplifying -55 + 2x + x2 = 0 Solving -55 + 2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '55' to each side of the equation. -55 + 2x + 55 + x2 = 0 + 55 Reorder the terms: -55 + 55 + 2x + x2 = 0 + 55 Combine like terms: -55 + 55 = 0 0 + 2x + x2 = 0 + 55 2x + x2 = 0 + 55 Combine like terms: 0 + 55 = 55 2x + x2 = 55 The x term is 2x. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2x + 1 + x2 = 55 + 1 Reorder the terms: 1 + 2x + x2 = 55 + 1 Combine like terms: 55 + 1 = 56 1 + 2x + x2 = 56 Factor a perfect square on the left side: (x + 1)(x + 1) = 56 Calculate the square root of the right side: 7.483314774 Break this problem into two subproblems by setting (x + 1) equal to 7.483314774 and -7.483314774.

Subproblem 1

x + 1 = 7.483314774 Simplifying x + 1 = 7.483314774 Reorder the terms: 1 + x = 7.483314774 Solving 1 + x = 7.483314774 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 7.483314774 + -1 Combine like terms: 1 + -1 = 0 0 + x = 7.483314774 + -1 x = 7.483314774 + -1 Combine like terms: 7.483314774 + -1 = 6.483314774 x = 6.483314774 Simplifying x = 6.483314774

Subproblem 2

x + 1 = -7.483314774 Simplifying x + 1 = -7.483314774 Reorder the terms: 1 + x = -7.483314774 Solving 1 + x = -7.483314774 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = -7.483314774 + -1 Combine like terms: 1 + -1 = 0 0 + x = -7.483314774 + -1 x = -7.483314774 + -1 Combine like terms: -7.483314774 + -1 = -8.483314774 x = -8.483314774 Simplifying x = -8.483314774

Solution

The solution to the problem is based on the solutions from the subproblems. x = {6.483314774, -8.483314774}

Solution

x = {6.483314774, -8.483314774}

See similar equations:

| 7(-8m+2)=-434 | | 4=-(x-7)+3 | | 21dy+6xy-6xv-21dv= | | 8x+(-5)=35 | | Y=1.03x | | 2y+3y+30+4x-100+x+5=360 | | f(1)=1(1)+3 | | vw+uw=uv | | 2x+(x+6)=54 | | -2a-6a=24 | | (w^2-4w+7)+(3w^2+5w-3)= | | 2y-36x=45-38y | | 1350=45x+30y | | 10=8-4y | | 3x*ln(x+3)+4=0 | | 11w+2(3w-1)=5 | | (9y-6)(1.5)+3.5y= | | 3.50x+40=57.50 | | 7n+n=64 | | 30x^2-25x=0 | | 2(2x+3)=24 | | -2c-24=2c-12 | | 9u-5u=36 | | 5x+2=-5 | | 6-3x=14x+2 | | 13=7r-6-2 | | 8p-6(1-2p)=86 | | x+(x+2)=116 | | n+4.1n+6=-1.5(n+4.8) | | -3(4x-8)=2-4(3x-7) | | -16x^2+64x-26=0 | | 3x-8=-24 |

Equations solver categories